Combating Substandard and Counterfeit Medicines by Securing the Pharmaceutical Supply Chain: The Drug Supply Chain Security Act (DSCSA) of 2013 - Le, Phuong (Innov Pharm, 2018)
On November 27, 2013, President Obama signed into law the Drug Quality Security Act (DQSA). Title II of the DQSA, the Drug Supply Chain Security Act (DSCSA), replaces all existing or future state-wide drug track or trace systems with a new federal drug tracing program that uses pedigrees and product identifiers for verification of the drugs being accepted by the buyer. While the full implementation of the DSCSA is projected to take about ten years from its enactment, both the implementation framework and milestones of the new federal tracing program have been carefully laid out. In this essay, we will explore the current state of the U.S. pharmaceutical supply chain and the imperatives behind the DSCSA. At the crux of this essay is an analysis of the DSCSA implementation plan, its challenges according to feedback from stakeholders, and its potential effectiveness against the entrance of substandard and counterfeit drugs into the U.S. pharmaceutical supply chain.